Dynamic vertical foreclosure with learning-by-doing production technologies - Frago Kourandi; Nikolaos Bettas (Games, 2024)
Here, we study vertical foreclosure in a dynamic setup with learning-by-doing production technologies. There is a downstream monopoly and an upstream duopoly, where manufacturers produce differentiated products and can gain proficiency through the accumulation of their production. We study the dynamic interactions in the vertical chain when the monopolist sets the prices; we find that customer foreclosure may arise in equilibrium when the products are close substitutes and be welfare-enhancing. The rate of learning is lower than the social optimal and a social planner would tend to impose exclusivity more often compared to the downstream monopolist.
Keywords: L42; L13; L14; L11; L81; 330; dynamic interactions; exclusivity; learning-by-doing